TEKNIK PEMBENIHAN IKAN KOMET (CARASSIUS AURATUS) DI UNIT PENGEMBANGAN BALAI BENIH IKAN AIR TAWAR (UPBBIAT) GONTORAN LOMBOK BARAT - APRYANY, RESSY ENY; DWIYANTI, SEPTIANA (Universitas Mahasaraswati K. Mataram, 2024)
One species from the Cyprinidae family that is very popular and highly developed in Indonesia is the comet fish (Carassius auratus). The main obstacle in comet fish production is the limited number of superior seeds. These obstacles are caused by improper handling of seeds related to larval rearing, such as air quality management, appropriate feed and fish mouth clearance as well as handling pests and diseases. The aim of this research is to understand and determine the process of hatching comet fish (Carassius aurataus) at the Freshwater Fish Seed Development Unit (UPBBIAT) Gontoran, West Lombok.The data obtained from Field Work Practice activities is explained descriptively, that is, it can be presented clearly and in detail. The number of eggs produced was 1,770. The number of eggs that successfully hatched was 1536 with a HR (Hatcing Rate) percentage of 81% and a final SR (Survival Rate) percentage of 84%.